Israel's military operations in Gaza telegenic lawfare and warfare - Hasian, Marouf Arif (Routledge studies in Middle Eastern politics, 2016)
Civilians in Gaza and Israel are caught up in complex, violent situations that have overstepped conventional battle lines. With its multidisciplinary approach and original analysis of the Israel/Gaza situation, this book will be of interest to students and scholars of Middle East studies and the Arab-Israeli conflict, as well as security studies and communication studies.